2018
DOI: 10.1155/2018/7328203
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Mobility in As-Containing Soils from Geogenic Origin: Fractionation and Leachability

Abstract: The lithogenic arsenic in soils of the Anllóns River basin (Spain) was quantified, its chemical fractions were determined, and its leachability characteristics were compared under various experimental conditions. Fifty soil samples of C horizons, sampling an area of 50 km 2 along the river course, were submitted to an exploratory analysis. Pseudo-total arsenic ranged between 2 and 489 mg kg −1 . Arsenic leachability using the standard methods DIN 38414-S4 and TCLP was less than 0.25% of pseudo-total As. Then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Soils are also enriched in arsenic in the mineralized areas, where concentrations of 4000 mg kg −1 have been detected [191]. In a wider study, total arsenic ranging between 2 and 489 mg kg −1 was determined in fifty soil samples of C-horizons, covering an area of 50 km 2 along the Anllóns River [68]. Arsenic leachability using the standard methods [192] and TCLP (Toxicity Characteristic Leaching Procedure) was less than 0.25% of total arsenic.…”
Section: The Anllóns River: Polluted Sediments Resulting From Former mentioning
confidence: 99%
See 1 more Smart Citation
“…Soils are also enriched in arsenic in the mineralized areas, where concentrations of 4000 mg kg −1 have been detected [191]. In a wider study, total arsenic ranging between 2 and 489 mg kg −1 was determined in fifty soil samples of C-horizons, covering an area of 50 km 2 along the Anllóns River [68]. Arsenic leachability using the standard methods [192] and TCLP (Toxicity Characteristic Leaching Procedure) was less than 0.25% of total arsenic.…”
Section: The Anllóns River: Polluted Sediments Resulting From Former mentioning
confidence: 99%
“…Alkalinity (pH >8.5) causes desorption or limited adsorption [66][67][68]. It has been observed that the adsorption of arsenic, like that of phosphate, decreases as the pH increases [69], although the release mechanisms at different pH depend on the experimental conditions, including Eh and the relative concentration of sorbents and the mineralogy and provenance of the sediment samples [66][67][68]. Specifically, in a study [70], it was observed that the percentage of arsenic released from sediments was 10 to 45 times higher at pH 10 than at pH 4.…”
Section: Adsorption/desorptionmentioning
confidence: 99%
“…In future research, our study will make full use of satellite and unmanned aerial vehicle remote sensing data to expand our research scope to obtain regional inversion results. Compared with the traditional spatial interpolation method based on many sampling points [ 43 , 44 ], the proposed algorithm combined with hyperspectral images to detect soil pollution is more economical and convenient. Moreover, based on the algorithm, other substances similar to arsenic (such as phosphorus) can also be included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilization of arsenic from rocks and soils into water bodies is of concern because it is a highly toxic element that poses serious threats to human and ecosystem health [39]. According to McBride [40] an element like As, which is more toxic to humans than to plants, poses a very insidious hazard to human health, as it may accumulate in crops to concentrations that are toxic to humans, while the crops do not show any signs of phytotoxicity.…”
Section: Arsenicmentioning
confidence: 99%
“…Arsenic is often an important component of gold deposits, and gold mining is frequently associated with arsenic pollution [39,41]. Processing of gold-bearing minerals that contain arsenopyrite or other arsenic-containing sulfide minerals can lead to the As pollution of water bodies.…”
Section: Arsenicmentioning
confidence: 99%